2019
DOI: 10.1007/s11240-019-01575-w
|View full text |Cite
|
Sign up to set email alerts
|

Stability and instability processes in the calli of Fagopyrum tataricum that have different morphogenic potentials

Abstract: The morphogenic callus (MC) of Fagopyrum tataricum contains a large amount of flavonoids, especially rutin, and exhibits a high level of antioxidant activity. A non-morphogenic callus (NC) may appear on the surface of the MC after two to three years of cultivation and is then subjected to a consistently high level of oxidative stress. The elucidation of the molecular background of this instability is essential for gaining a better understanding of the somaclonal variation mechanisms in tissue cultures that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Such a detailed analysis of the spatio-temporal chemical composition of the ECM will contribute to the knowledge about the surface layer that covers a callus that has a different morphogenic potential (Šamaj et al 2008;Endress et al 2009;Betekhtin et al 2019). These results are presented for the first time (at least to the best of our knowledge) for the A. arguta callus.…”
Section: Chemical Composition Of Ecm and Cell Wall As A Marker For DImentioning
confidence: 85%
“…Such a detailed analysis of the spatio-temporal chemical composition of the ECM will contribute to the knowledge about the surface layer that covers a callus that has a different morphogenic potential (Šamaj et al 2008;Endress et al 2009;Betekhtin et al 2019). These results are presented for the first time (at least to the best of our knowledge) for the A. arguta callus.…”
Section: Chemical Composition Of Ecm and Cell Wall As A Marker For DImentioning
confidence: 85%
“…As has been shown in previous studies, analyses of the distribution and changes in the signal intensity of epitopes can be compared with the expression profiles of the genes encoding the proteins that are targeted by these antibodies [15,34]. In this work, we focused on the FLA that have been implicated in modulation of signalling upstream of cell wall polymer biosynthesis, remodelling, as well as in the stress response as one of the AGP sub-families [35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the embryogenic callus of B. distahyon revealed that AGP epitopes, which were recognized by the JIM16 and LM2 antibodies, were positive markers of embryogenic cells [ 25 ]. For the Fagopyrum tataricum embryogenic callus, it was demonstrated that the AGPs epitope recognized by the LM2 antibody was a positive marker of the embryogenic cells [ 47 ]. Studies during the SE of Arabidopsis reported that the JIM16 AGP epitope appeared to be a marker of embryogenic cells [ 29 ].…”
Section: Cell Wall Composition As a Marker Of Changes In Cell Fate Du...mentioning
confidence: 99%
“…Extensin/HRGP glycoprotein Musa spp. embryogenic cells and nonembrygenc cells [40] Phalaenopsis embryogenic cells [42] Brachypodium distachyon embryogenic calli [25] Actinidia arguta embryogenic and nonembryonic cells [43] JIM12 Extensin/HRGP glycoprotein Dactylis glomerata embryogenic calli [41] Actinidia arguta embryogenic and nonembryonic cells [43] Brachypodium distachyon nonembryonic cells [25] AGP JIM8 Arabinogalactan Arabidopsis thaliana explant cells [29] Daucus carrota nonembryonic cells [26] JIM4 Arabinogalactan glycoprotein, βGlcA-(1,3)-αGalA-(1,2)-Rha Arabidopsis thaliana explant cells [29] LM2 Arabinogalactan protein, carbohydrate epitope containing β-linked GlcA Quercus suber proembryogenic masses, somatic embryos [28] Brachypodium distachyon embryogenic calli [25] Fagopyrum tataricum embryogenic cells [47] Arabidopsis thaliana explant cells [29] Daucus carrota meristematic/pluripotent cells [26]…”
Section: Jim20mentioning
confidence: 99%